SEMANTIC FOUNDATIONS OF PUNCTUATION IN ENGLISH: BASED ON THE MATERIALS OF DRAMATIC WORKS - Mansurova Zarifa Olimjonovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the semantic role of punctuation in English, focusing on how  punctuation  marks  contribute  to  meaning  and  interpretation  within  dramatic works. By analyzing the use of punctuation in dialogue and stage directions, the study investigates how these seemingly small marks influence pace, tone, characterization, and the overall understanding of dramatic texts. The research argues that punctuation is not merely a grammatical convention, but a crucial tool for playwrights to convey nuances  of  meaning  and  create  specific  effects  for  the  audience.  The  analysis  will consider the use of commas, semicolons, colons, dashes, ellipses, question marks, and exclamation  marks,  examining  how  their  strategic  deployment  shapes  the  reader's experience  and  informs  performance.  Ultimately,  this  study  aims  to  illuminate  the complex interplay between punctuation, language, and dramatic expression.